FITTING FORMULAS OF AMPLITUDE OF CENTRAL PRESSURE AND PRESSURE SPIKE OF LINE CONTACT EHL STATE - ZHANG XinLei; XIA BoQian (Jixie qiangdu)
The effects of load,speed and material parameters on the amplitude of central pressure and pressure spike were investigated under line contact EHL condition. Based on the analysis of mass numerical data and regression,the fitting formulas of amplitude of central pressure and pressure spike of line contact EHL state were proposed and the accuracy of fitting formulas was verified. The result shows that in a fairly wide range of the parameters,the accuracy of fitting formulas is satisfactory,which can completely meet the demands of engineering designs.